Zinc Sensitizes Lung Cancer Cells to Anoikis through Down-Regulation of Akt and Caveolin-1. (17th February 2016) - Pramchu-em, Chalamart; Meksawan, Kulwara; Chanvorachote, Pithi
ABSTRACT: Anoikis is a particular type of apoptosis induced by the loss of cell attachment from extracellular matrix. It has been shown to play a critical role in the inhibition of cancer metastasis. Herein, we report for the first time that zinc, an essential trace element, has anoikis sensitizing activity against lung cancer cells. An anoikis assay showed that zinc treatment at the concentrations of 0–50 µM enhanced the anoikis response in human lung cancer H460 cells with significant decreased cell viability and increased number of apoptosis cells detected with Hoechst 33342 and PI co-staining assay. Moreover, zinc significantly inhibited the growth of cancer cells in an anchorage-independent condition. This is mediated through the zinc-induced decrease in prosurvival active protein kinase B (Akt) and metastasis-regulating caveolin-1 (Cav-1) protein expression. Taken together, our results indicate that zinc sensitizes non-small cell lung cancer cells to anoikis and may play a role in the prevention of cancer metastasis.